Sub Controller Design on KRSBI Humanoid R-SCUAD Robot Sub Controller Design on KRSBI Humanoid Robot R-SCUAD - Mizan, Bahrul; Satya Widodo, Nuryono (Association for Scientific Computing Electrical and Engineering (ASCEE), 2022)
The purpose of this research is to design OpenCM9.04 controllers such as Arbotix (Pro) with MPU-9250 sensor as robot balance, as well as controlling the movement of DYNAMIXEL servo angles based on camera input on the robot, the Design of the OpenCM9.04 controller board on the robot consists of 2 main components namely OpenCM9.04 which works as a mini system and OpenCM 485 Expansion Board that works as a conference to the serial that provides interface to buttons and LEDs as well as a power supply circuit , where OpenCM9.04 as the main controller then sends data to OpenCM 485 which will process the MPU-9250 sensor as well as the DYNAMIXEL servo on the robot. The hardware system design consists of an MPU-9250 sensor to maintain balance in the robot so that the robot does not fall when walking or running and servo DYNAMIXEL to move the corners on the robot. The results obtained by the OpenCM9.04 controller have been successfully developed and tested on robots in the KRSBI-H racetrack and the robot has been able to maximize in the game well without any constraints on the microcontroller used.